2020
DOI: 10.2106/jbjs.oa.19.00043
|View full text |Cite
|
Sign up to set email alerts
|

Dual Versus Single-Plate Fixation of Midshaft Clavicular Fractures

Abstract: AllisThe purpose of this form is to provide readers of your manuscript with information about your other interests that could influence how they receive and understand your work. The form is designed to be completed electronically and stored electronically. It contains programming that allows appropriate data display. Each author should submit a separate form and is responsible for the accuracy and completeness of the submitted information. The form is in six parts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 24 publications
0
26
0
1
Order By: Relevance
“…Allis et al reviewed 44 patients with midshaft clavicle fractures managed with either 3.5-mm superior plating or dual mini-fragment plate fixation [16]. Reoperation rates were significantly lower in patients managed with dual mini-fragment plates than those managed with a 3.5-mm superior plate, primarily due to less frequent metalware irritation (0% vs. 29%, p = 0.008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allis et al reviewed 44 patients with midshaft clavicle fractures managed with either 3.5-mm superior plating or dual mini-fragment plate fixation [16]. Reoperation rates were significantly lower in patients managed with dual mini-fragment plates than those managed with a 3.5-mm superior plate, primarily due to less frequent metalware irritation (0% vs. 29%, p = 0.008).…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of dual plating may be twofold: firstly, improved strength may reduce construct failure, and secondly, stronger constructs may allow the use of minimally prominent low-profile plates. Allis et al recently compared dual mini-plates to standard superior plates for midshaft clavicle fractures and found significantly fewer reoperations for metalware irritation in the dual mini-plate cohort [16]. Few biomechanical studies exist comparing these constructs.…”
Section: Introductionmentioning
confidence: 99%
“…Non-union was reported in 10 studies. [29][30][31][45][46][47][49][50][51][52] The overall non-union rate was 3.4%, with 0.8% (N ¼ 254) of dual plated and 2.9% (N ¼ 339) of single plated clavicles going on to nonunion. Pooled comparison across the five comparative studies 45,46,49,51,52 demonstrated no significant difference in the odds of fracture non-union with dual and single plate fixation methods (OR, 0.60; 95% CI, 0.13 to 2.79; P ¼ 0.52) (Figure 2(a)).…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Complications. Complications were described in 10 studies [29][30][31][45][46][47][48][49][50][51] and included intraoperative and postoperative complications such as neurovascular injury and infection. Complications were defined in a heterogenous manner across studies, as such, we defined a complication as an unintended negative outcome other than non-union, delayed union, and reoperation, which were reported separately in this review.…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation